Practice long cases for the Part B Final FRCR Examination - Davidson, Jennifer (MasterPass, 2013)
This succinct examination guide and DVD contain over 4700 radiological images allowing for many more opportunities, using the print-off examination format sheet and digital images, to recreate examination conditions. Model sample answers are provided for each question to aid in self-marking and revision. With a complete introduction to the examination including the marking scheme and top tips for success, candidates will welcome the chance to practise papers and check their examination technique in this unique guide